Preservation of lower extremity spare parts using the University of Wisconsin solution. (January 2019) - Alnaif, Nayif; Lee, James; Azzi, Alain Joe; Aldekhayel, Salah; Zadeh, Teanoosh
The management of a mangled limb is a challenging endeavor. With the advancement in microsurgery, spare parts surgery (fillet flaps) has gained recent interest. In the context of lower extremity amputation secondary to trauma, viable spare parts can provide stump soft tissue coverage, potentially preserving critical length and obviating above-knee amputations. Commonly, spare parts surgery is performed in the acute setting but tissue preservation is sometimes necessary. The authors report their experience preserving a fillet flap of a mangled lower extremity for 48 h using the University of Wisconsin solution. A sole fillet flap and a split-thickness skin graft were harvested and preserved from the amputated lower extremity (based on the posterior tibial artery and vein). Stump coverage was achieved by anastomosing the fillet flap to the proximal posterior tibial artery and vein. This solution has not been previously described for preservation of fillet flaps.